An Analysis of Product Dimensions Out of Specification as Quality Claim Improvement Activity : Application of 8D Method in the Injection Plastic Industry - Lubas Wahyudi, Pongky; Wulandari, Anita (JMPM (Jurnal Material dan Proses Manufaktur), 2020)
Every company tries to find ways to maintain its market position in an increasingly competitive business environment. In order to be successful, companies need to achieve their objectives and goals to make their vision a reality while adhering to their mission. Company claims report in the few years still hasn’t solved yet. Such complaints are significant because customersatisfaction can only be improved if the root causes of the problem is clearly identified. In the plastic industry that produces parts for the automotive industry, a systematic method named 8D is used to analyze product conformity to specifications. The 8D method consists of nine disciplines problem-solving. The original purpose of 8D method was to eliminate the defect causing the problem, thus restoring customer satisfaction and level up the quality level of the company. This research established the suitability of the 8D for complaint settlement. 8D involves teamwork to solve the problem and using a 9-step structural approach. This case study resulted that the 8D is effective. The total customer claims at the end of last year until this year in Dec 2020 totaled zero (0) and process rejection for incorrect dimensions were reduced from 0.07 % to 0.01%.